HUBUNGAN KINERJA PEGAWAI LOKET TERHADAP KEPUASAN PASIEN DI PUSKESMAS CAKRANEGARA - Sujarwoko, Sujarwoko; Maria Sarima Didung (LPPM, Akademi Administrasi Rumah Sakit Mataram, 2022)
Cakranegara Health Center is one of the health centers in the city of Mataram. This health center serves both inpatients and outpatients, each service institution has different services to patients. This study uses quantitative research methods with a total of 97 respondents. The results of the analysis as many as 10 patients said the employee performance was of poor quality or 10.3%, while 52 patients said that the employee's performance was of high quality or could be percentage to 53.6%, and the patients who said that the employee's performance was very high quality were 35 patients or 36.1%. The sample in this study was 97 respondents at the Cakranegara Health Center, the value of the respondents' answers to employee performance on patient satisfaction from 18 questions listed on the questionnaire distributed to 97 respondents. The results obtained, namely the value = 0.076, which means that it is smaller than 0.05, this indicates that there is a relationship between the performance of the employee at the registration counter and patient satisfaction at the Cakranegara Health Center. From the results of the p value (Sig) = 0.000 <0.05 (significant). This means that there is a significant relationship between the performance of employees at the registration counter and patient satisfaction at the Cakranegara Health Center in 2021. Performance is everything that a person does and the results in carrying out the function of a job. The results of quantitative analysis research at the Cakranegara Health Center found that there were still unsatisfactory services to patients in registration services at the Cakranegara Health Center. Patient satisfaction can be seen from the services provided by the registration counter employees, where the perception of patients who feel that employee performance is less qualified is 100% less. satisfied 50%, satisfied 40%, and very satisfied 10%. And it is recommended for further researchers to specifically examine the performance of services provided by employees at the registration counter.